2009
DOI: 10.4161/cbt.8.16.8963
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of DACH1 and cyclin D1 in endometrial cancer

Abstract: The altered expression of human DACH1, a Drosophila Dachshund homolog, has been associated with tumor progression and metastasis. DACH1 inhibits breast cancer cellular proliferation via cyclin D1. Endometrial cancer is the third most common cancer in women and broad screening for DACH1 expression will further our understanding of this disease. Herein, we screened 126 hysterectomy specimens for DACH1 expression and evaluated the correlation between DACH1 levels and several clinical parameters. Decreased DACH1 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
49
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 41 publications
5
49
0
Order By: Relevance
“…Loss of DACH1 expression and increased oncogenic FOX protein expression could lead to deregulation of a subset of genes required for tumorigenesis. We had previously shown that loss of DACH1 expression in human breast and endometrial cancers predicts poor outcome (2,6). Future studies will address whether loss of DACH1 correlates with increased FOXM1 expression during the progression of breast and endometrial cancers as well as other type of cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of DACH1 expression and increased oncogenic FOX protein expression could lead to deregulation of a subset of genes required for tumorigenesis. We had previously shown that loss of DACH1 expression in human breast and endometrial cancers predicts poor outcome (2,6). Future studies will address whether loss of DACH1 correlates with increased FOXM1 expression during the progression of breast and endometrial cancers as well as other type of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Altered expression or function of mammalian RDGN components have been described in human tumors (1)(2)(3)(4)(5). DACH1 is expressed widely in normal adult tissues, and loss of DACH1 expression in human breast and endometrial cancers predicts poor outcome (2,6). DACH1 blocks c-Jun-induced DNA synthesis, reverts the H-Ras and c-Myc-induced oncogenic phenotype in the immortalized human breast epithelial cell line, and inhibits breast tumor metastasis in mice (2,7).…”
mentioning
confidence: 99%
“…Clinical studies have demonstrated a correlation between poor prognosis breast cancer and reduced expression of the cell fate determination factor DACH1 (13), and loss of DACH1 expression has been observed in prostate and endometrial cancer (14,15). Several lines of evidence suggest Dachshund may function as a tumor suppressor.…”
Section: /Cd24mentioning
confidence: 99%
“…Vertebrate homologs of ey (Pax6), so (Six), eya (Eya), and dac (DACH1) have been identified, and the human DACH1 (Dach1 in mice) gene encodes a protein composed of two highly conserved domains, dachshund domain 1 (DD1, also known as Box-N) with a predicted helix-turn-helix structure, and dachshund domain 2 (DD2, also known as Box-C). Altered expression of DACH1 has been reported in a variety of human tumors (5)(6)(7)(8)(9). DACH1 is expressed widely in normal epithelial tissues, and reduced DACH1 expression predicts poor outcome of breast and endometrial cancer patients (6,9).…”
mentioning
confidence: 99%
“…Altered expression of DACH1 has been reported in a variety of human tumors (5)(6)(7)(8)(9). DACH1 is expressed widely in normal epithelial tissues, and reduced DACH1 expression predicts poor outcome of breast and endometrial cancer patients (6,9). DACH1 represses TGF-␤ signaling, reduces DNA synthesis, and reverts the tumorigenic phenotypes induced by the oncogenes such as ErbB2, Ras, Src, and Myc in human mammary cell lines (10,11).…”
mentioning
confidence: 99%